Thin-walled composite beam cross-sectional analysis using the mechanics of structure genome. (July 2020) - Deo, Ankit; Yu, Wenbin
Abstract: Quick and accurate predictions of cross-sectional properties are required in the preliminary design of thin-walled composite beams. Existing literature provides accurate analytical solutions to the problem, albeit limited to open and single cell sections with stress continuity constraints imposed. Mechanics of structure genome has been used to develop an asymptotically correct model for thin-walled open, closed, single and multi-cell cross sections consisting of any arbitrary anisotropic material without imposing any additional conditions. In this paper, Euler-Bernoulli thin-walled beam cross-sectional model is developed in a finite element framework and demonstrated using several examples, followed by a comparison with existing approaches. Highlights: Applied MSG to model thin-walled beams for the first time using degenerated elements. Addressed multi-cell problem with no additional constraints. Improved accuracy of results by considering off-centric reference axis of plate segments. Reduced computational power for calculating thin-walled cross-sectional properties. Generated beam properties for realistic wind turbine blade with more than 50 layers.